Penatalaksanaan Pasien Tinea Korporis Pembuat Kerupuk Dengan Pendekatan Kedokteran Keluarga - Fauzia Tria Andara Sari; Dian Isti Angraini (Majority, 2020)
Tinea corporis is an infectious skin infection caused by dermatophytes that colonize and obtain nutrients from keratin, causing infections in the skin in the form of inflammatory reactions. The incidence of tinea corporis is high in tropical and subtropical climates as well as in populations with low socioeconomic status who live in crowded environments and low hygiene. The diagnosis of tinea corporis is based on history taking and physical examination. This case will discuss the identification of risk factors, management and prevention of tinea corporis in cracker makers based on patient-centered and family approach. This study is a case study with data obtained from history taking, physical examination, home visits, and patient medical records. Case, 30-year-old woman works as a cracker maker, lives in a main family, with a moderate daily activities, lack of personal hygiene and environment, and good relations between family members. The patient complained of itching accompanied by a burning sensation and redness around the side folds of the breast, back and right thigh since about 1 week before coming to the health center. After a holistic intervention with the educational method, it can be seen that there are good developments in patients ranging from decreased clinical symptoms to changes in good behavior towards personal and environmental hygiene, conclusions, family medicine services are effective in the management of tinea corporis. Providers resolve clinical problems and also deal with internal, external, psychosocial and environmental risks.